Visita de abejas (Apis mellifera, Hymenoptera: Apoidea) a flores de melón Cucumis melo (Cucurvitaceae) en Panamá - Carlos Di Trani de la Hoz, Juan (2007)
Flower visits by bees were observed in a melon cultivated field of San Lorenzo district, in Chiriquí, Panama, from January 6 to February 19, 2002, from 6:30 am to 4:30 pm We recorded the duration of each foraging event and the type of resource collected. Flower visits were mostly for nectar collection (∼75 %). Pollen foraging was concentrated in the first hours of the morning and ended by 11:00 am The mean collection time was similar for both food resources, but was different between flower sexes. Flower visits to female flow-ers took longer (Student's t test, p<0.0001), with a mean time duration of 8.4±4.4 s, whereas in male flowers mean visitation time was of 4.0±1.5 s. Finally, the mean time for each floral sex remained practically constant through the evolution of the crop. Our results were similar to the found ones in temperate zone crops, so appar-ently tropical conditions of Panama do not change the bee visit patterns on melon flowers.